A framework structure to enhance the implementation of private finance initiative (PFI) projects in Malaysia at pre-construction stage: a methodological development / Shamsida Saidan Khaderi, Abdul Rashid Abd Aziz and Ani Saifuza Abd Shukor. - Khaderi, Shamsida Saidan; Abd Aziz, Abdul Rashid; Abd Shukor, Ani Saifuza (Universiti Teknologi MARA , Shah Alam: Faculty of Architecture, Planning and Surveying, 2018)
Private finance initiative (PFI) in Malaysia has been inundated by various controversies and criticisms from the very beginning. Yet, in-depth researches relating to them have been lacking. Based on the circumstances, the paper proposes a framework structure to enhance the implementation of PFI projects in Malaysia with focus on the pre-construction stage with the following objectives: to determine the issues and constraint which have arisen, to determine the success factors and lastly to develop a framework for performance improvement. Semistructure interviews with 35 experts and nine case studies (each three representing Modes 1, 2 and 3) were used to collect data. The study found ten success factors which is: fair risk distribution, public-private cooperation, comprehensive output specification, value for money, maintenance culture, innovation, performance-based payment, cost linked to life span, transparency and financing. A workable implementation framework for the pre-construction stage was developed after industry practitioners tested it. This framework can help industry players including contractors in making sound decisions when undertaking PFI projects.